Meal taking behaviors at work and their associated factors among Faculty of Medicine and Health Sciences staff, UPM 2017 - Ebrahim, Ebrahim Mohammed Abdullah (2017)
Food is important for thoughts, productivity, and health. Workers spend half of their waking hours in weekdays at work and this long time can contribute to their health positively or negatively. Meal taking behaviors at workplaces are important to be assessed as this may lead to determination of the current situation and to future interventions improving working conditions and nutrition of workers. This study was conducted to determine the meal taking behaviors status at work of the Faculty of Medicine and Health Sciences Universiti Putra Malaysia staff (FMHS, UPM).